European Gravity Service for Improved Emergency Management (EGSIEM)—from concept to implementation. Issue 3 (27th May 2019) - Jäggi, Adrian; Weigelt, M; Flechtner, F; Güntner, A; Mayer-Gürr, T; Martinis, S; Bruinsma, S; Flury, J; Bourgogne, S; Steffen, H; Meyer, U; Jean, Y; et al.
SUMMARY: Earth observation satellites yield a wealth of data for scientific, operational and commercial exploitation. However, the redistribution of mass in the system Earth is not yet part of the standard inventory of Earth Observation (EO) data products to date. It is derived from the Gravity Recovery and Climate Experiment (GRACE) mission and its Follow-On mission (GRACE-FO). Among many other applications, mass redistribution provides fundamental insights into the global water cycle. Changes in continental water storage impact the regional water budget and can, in extreme cases, result in floods and droughts that often claim a high toll on infrastructure, economy and human lives. The initiative for a European Gravity Service for Improved Emergency Management (EGSIEM) established three different prototype services to promote the unique value of mass redistribution products for Earth Observation in general and for early-warning systems in particular. The first prototype service is a scientific combination service to derive improved mass redistribution products from the combined knowledge of the European GRACE analysis centres. Second, the timeliness and reliability of such products is a primary concern for any early-warning system and therefore EGSIEM established a prototype for a near real-time service that provides dedicated gravity field information with a maximum latency of 5 d. Third, EGSIEM established a prototype of a hydrological/early warning service that derives wetness indices as indicators of hydrological extremes and assessed their potential for timely scheduling of high-resolution optical/radar satellites for follow-up observations in case of evolving hydrological extreme events.